Competence of Croatian Student-Teachers and Primary School Teachers in the Visual Arts - Zlata Tomljenović; Svetlana Novaković (Center for Educational Policy Studies Journal)
In visual arts education, specific competences pertain to having knowledge from the theory and praxis of visual arts and the teaching methodology of visual arts. The goal of this research was to examine the opinions of 231 students of graduate teacher studies and 143 in-service primary school teachers about the importance of specific competences in the visual arts, as well as the level of achieving the stated competences during studies. The frequency of teachers attending various forms of professional training in the visual arts was also examined. Two questionnaires were designed for the research. The data obtained with the questionnaires were processed at the level of descriptive and inferential statistics. A Wilcoxon Signed Ranks Test was used to compare the differences in the arithmetic means between the perception of importance and the perception of possessing the competences between these two groups. The research has shown the existence of a statistically significant difference between the self-assessment about the importance of specific competences in the visual arts, and the self-assessment of having these competences, both with students of the Croatian faculties of teacher education and primary school teachers. The results also have shown the insufficient presence of teachers’ further professional training in the visual arts area.